DNA AND RNA CONTENT IN SOME TISSUES OF FRESHWATER FISH NOTOPTERUS NOTOPTERUS EXPOSED TO COPPER SULPHATE - K. RAVIKIRAN; R. S. KULKARNI (The Bioscan, 2012)
The nucleic acid (DNA and RNA) content in different tissues such as brain, liver, kidney and ovary of copper sulphate exposed freshwater fish, Notopterus notopterus has been studied. The changes in the nucleic acid content of the tissues have been observed. The DNA content in the ovary is higher in comparison to other tissues. The variation of DNA content in control and copper sulphate exposed fish is ovary >liver>brain>kidney. The RNA content also exhibited similar to that of DNA, having higher amount in the ovary and the variation is ovary >liver>brain>kidney. Although the degree of variation between the tissue remains same in both control and experimental groups, the nucleic acid content reduced under copper sulphate exposed freshwater fish, Notopterus notopterus indicating copper sulphate as a pollutant effect the nucleic acid content in the tissue.